DEPENDENCE OF A GAS-PHASE DNA GLOBULE SIZE ON CHAIN LENGTH - T. N. Goryachkovskaya; A. S. Kozlov; V. M. Popik; N. A. Kolchanov; S. E. Peltek (Вавиловский журнал генетики и селекции)
Modern trends in using DNA in nano- and biotechnologies generated the need for new methods of analyzing DNA molecules with up-to-date equipment. We developed a method of mild nondestructive ablation with terahertz radiation for bringing DNA molecules to aerosol. DNA nanoparticles were measured in the gas phase with a diffusion aerosol spectrometer. Changes that happen to DNA in the gas phase were visualized by atomic force microscopy (AFM). Comparison of diffusion sizes of plasmid pUC18 aerosol particles with those obtained by AFM indicated that DNA molecules experienced condensation in the gas phase. We constructed a model on the base of modern concepts of DNA condensation and globule formation. The predictions matched well the experimental data. The persistence DNA length estimated in the gas phase was about 0.5 nm. This fact points to the absence of distributed charge on the DNA surface in the gas phase and the nonionizing habit of terahertz radiation. Study of DNA conformations in the gas phase will add to the understanding to DNA compactness under natural and artificial conditions.